THE EU INSTITUTIONAL MODEL OF COMPETITION LAW ENFORCEMENT REVISITED: HOW MUCH RULE OF LAW SUFFICES? - Marković-Bajalović, Dijana (Pravni zapisi, 2022)
The EU model of competition law enforcement has been criticized by many authors ever since antitrust provisions in the EEC Treaty became effective. The fundamental contradiction between the high level of fines threatened (and often imposed) for antitrust violations and the administrative, inquisitorial procedure for investigating antitrust offences and imposing sanctions has principally inspired the critics. The compatibility of the EU model with Article 6 of the European Convention on Human Rights (the ECHR) was disputed, instigating the EU institutions to take steps to improve the institutional and procedural framework for applying competition rules. This process has not been completed yet. Directive 2019/1 raised additional controversies regarding the compliance of variegated national enforcement models with the rule of law.This article aims to analyze the genesis of the competition enforcement model in the EU, which materialized mainly through the EU secondary legislation and ECJ case law. We evaluate the EU model against the enforcement system imagined by the Ordoliberal school of thought and, secondly, against administrative models existing in two “old” Member States, in which the rule of law has deeply rooted – France and Germany. We conclude by identifying the most cumbersome deficiencies of the EU model and proposing possible solutions for eliminating them.
Keywords: competition law; administrative enforcement; Ordoliberal school of thought; the rule of law; Article 6 of ECHR; Directive 2019/1; Menarini decision